(untitled) (Journal of Comparative & International Higher Education, 2024)
With academic capitalism as a framework, we conducted a qualitative study with a phenomenological approach to explore higher education leaders’ perceptions of internationalization during the initial stages of the Covid-19 shutdown in 2020. The study’s findings indicate that, overall, administrators value internationalization as a process that creates quality educational programming. However, leaders are influenced by institutions’ cultures and priorities, and they feel isolated as they seek to appeal to constituents to promote internationalization. Aware of the increasing use of commercial models and emphasis on generating revenue to compensate for funding shortfalls, higher education leaders vacillate from emphasizing revenue to promoting educational and social value. Upper-level administrators prioritize articulated institutional commitment and administrative leadership for internationalization over curriculum and faculty policies and practices. Overall, upper-level administrators value internationalization.